Metformin protects against intestinal ischemia-reperfusion injury and cell pyroptosis via TXNIP-NLRP3-GSDMD pathway - Yifan Jia; Ruixia Cui; Cong Wang; Yang Feng; Zeyu Li; Yingmu Tong; Kai Qu; Chang Liu; Jingyao Zhang (Redox Biology, 2020)
Intestinal ischemia-reperfusion (I/R) injury is a life-threatening vascular emergency and has long been a disturbing problem for surgeons. Oxidative stress is considered a vital factor in I/R injury. Metformin has anti-oxidative properties and protects against I/R injury. The present study aimed to investigate whether Metformin protects against intestinal I/R injury and reveal the protective mechanism of Metformin. I/R injury was induced in mice by temporary superior mesenteric artery occlusion, and Caco-2 cells were subjected to OGD/R to establish an in vitro model. Different doses of Metformin were administered in vivo and in vitro. We found that I/R injury led to intestinal barrier disruption and cell death by examining histopathological results and the intestinal barrier index, including TER, tight junction proteins and serum biomarkers. We confirmed the existence of pyroptosis in intestinal I/R injury. Moreover, we confirmed the role of pyroptosis in intestinal I/R injury by silencing the gasdermin D (GSDMD). Then, we confirmed that Metformin treatment protected barrier function against intestinal I/R injury and reduced oxidative stress and the inflammatory response. Importantly, Metformin reduced pyroptosis-related proteins, including NLRP3, cleaved caspase-1, and the N-terminus of GSDMD. Knocking down the GSDMD could reversed the protective effects of Metformin, which showed pyroptosis was one of the major cell death pathways controlled by Metformin treatment in setting of intestinal I/R injury. We also discovered that Metformin suppressed the expression of TXNIP and the interaction between TXNIP and NLRP3. We performed siRNA knockdown and found that the protective effects were abolished, which further confirmed our findings. In conclusion, we believe that Metformin protects against intestinal I/R injury in a TXNIP-NLRP3-GSDMD-dependent manner.